Incidence and antibiotic prescribing for clinically diagnosed urinary tract infection in older adults in UK primary care, 2004-2014 - Ahmed, H; Farewell, D; Jones, H; Francis, N; Paranjothy, S; Butler, C (Public Library of Science, 2018)
Urinary tract infections (UTI) are an important cause of morbidity and antibiotic use in older adults but there are little data describing disease burden in primary care. The aim of this study was to estimate the incidence of clinically diagnosed UTI and examine associated empirical antibiotic prescribing. We conducted a retrospective observational study using linked health records from almost one million patients aged ≥65 years old, registered with 393 primary care practices in England. We estimated incidence of clinically diagnosed UTI between March 2004 and April 2014, and used multilevel logistic regression to examine trends in empiric antibiotic prescribing. Of 931,945 older adults, 196,358 (21%) had at least one clinically diagnosed UTI over the study period. In men, the incidence of clinically diagnosed UTI per 100 person-years at risk increased from 2.81 to 3.05 in those aged 65–74, 5.90 to 6.13 in those aged 75–84, and 8.08 to 10.54 in those aged 85+. In women, incidence increased from 9.03 to 10.96 in those aged 65–74, 11.35 to 14.34 in those aged 75–84, and 14.65 to 19.80 in those aged 85+. Prescribing of broad-spectrum antibiotics decreased over the study period. There were increases in the proportion of older men (from 45% to 74%) and women (from 55% to 82%) with UTI, prescribed a UTI specific antibiotic. There were also increases in the proportion of older men (42% to 69%) and women (15% to 26%) prescribed antibiotics for durations recommended by clinical guidelines. This is the first population-based study describing the burden of UTI in UK primary care. Our findings suggest a need to better understand reasons for increasing rates of clinically diagnosed UTI and consider how best to address this important clinical problem.